Review of C. Daniotti, Reinventing Alexander: Myth, Legend, History in Renaissance Italian Art, Turnhout, Brepols (2022). - Borja Antela (Karanos)
Claudia Daniotti, Reinventing Alexander: Myth, Legend, History in Renaissance Italian Art, Turnhout, Brepols, 2022, 348 pp [ISBN 978-2-503-59743-0].